The politics of cultural difference in northern Cameroon - Burnham, Philip (International African library, 1996)
This study, based on research spanning 25 years, focuses on the shifting patterns of social assimilation and exclusion that have characterised the inter-ethnic relations of North Cameroon for almost two centuries.